Analysis of Mining Engineering Students’ Knowledge, Attitudes and Practices on Occupational Safety and Health in Mining Industry Field - Sunandar, Suwarto; Yodang, Yodang (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The mining industry has booming all over the world including developing countries such as Indonesia. Occupational safety and health was the main issue related to mining industry workers. As mining engineering students who will work in the mining industry field, it was important to identify the readiness of the students work in the mining industry field. This study aims to investigate students’ knowledge, attitude and practices on OSH in the mining industry field. This study conducted with a cross-sectional survey method, and mining engineering students who actively during the semester as the target population of the study. There are 56 students who participate in this study and all participants recruited voluntarily online. Data analyzed used the Chi-square and Mann-Whitney test. The study finding that there are 73.2% of participants have adequate knowledge, 96.4% have a positive attitude, and 51.8% have good practices on OSH.  For the knowledge domain, the student's level (p=0.047), fieldwork experiences (p=0.040), interest in OSH issue for research (p=0.032), and webinar attendance (p=0.049) are significantly associated with students’ knowledge on OSH. For the practice domain, fieldwork experiences (0.013), interest in OSH issue for research (p=0.021), and webinar attendance (p=0.022) are significantly affecting the students’ practice on OSH. In conclusion, improving students' knowledge, attitude and practices on OSH in mining industry fields was crucial and essential in order to reduce work-related accidents and diseases.